Studies on Quality Characters of Selected Fruits and Vegetable in Wholesale Market of Bhopal - Singh, Sunita; Kulkarni, S D (Journal of Agricultural Engineering, 2003)
Texture and colour grades of tomato, mango and banana were studied. Large variations in colour and texture of the commodities were observed in different months. These were graded into raw, ripe and over-ripe grades. Bananas seemed to be the toughest ones as transported and transacted raw (135.23 N). However, these were most delicate in texture when ripe (14.09 N). Tomatoes showed a textural range from 3.98 N to 70.02 N. Mangoes differed due to maturity and variety. The raw (Kert) were hard (&gt64.06 N), whereas ripe mango Langra varieties firmer (13.94 N) than ripe Dasehri variety (12.25 N). Over-ripe mangoes were soft [3.57 N (Badam); 4.47 N (Totapari)). All of these commodities were affected by rough handling, packaging and transport conditions.